Diet Quality Scores and Asthenoteratozoospermia Risk: Finding From a Hospital-Based Case–Control Study in China - Cui, Qi; Wang, Hui-Han; Wu, Qi-Jun; Wang, Xiao-Bin; Guo, Ren-Hao; Leng, Xu; Tan, Xiao-Ling; Du, Qiang; Pan, Bo-Chen (Frontiers in Nutrition, 2022)
Objective We aimed to examine associations of diet quality scores, including the dietary approaches to stop hypertension (DASH), alternate Healthy Eating Index (AHEI), and Chinese Healthy Eating Index (CHEI) with asthenoteratozoospermia risk in China. Methods Among 254 cases and 633 controls in a hospital-based case–control study in Shenyang, Liaoning Province, China, DASH, AHEI, and CHEI were calculated using a validated food frequency questionnaire. Asthenotetrazoospermia was evaluated according to World Health Organization guidelines. Unconditional multiple logistic regression was used to estimate odds ratios (ORs) with 95% confidence intervals (CIs) for the association between quality diet scores and asthenoteratozoospermia risk. Results We found that the CHEI score was inversely associated with asthenoteratozoospermia risk, with ORs of 0.59 (95% CI 0.39, 0.88) and 0.59 (95% CI 0.39, 0.88) for the 2nd and 3rd tertiles vs. the 1st tertile, respectively (P trend < 0.05). In addition, our data indicated that each standard deviation increase in CHEI, AHEI-2010, and DASH score was associated with 19, 13, and 17% decreased risk of asthenoteratozoospermia, respectively. Conclusion Our findings suggest that higher adherence to the CHEI, AHEI-2010, and DASH diet quality scores may reduce the risk of asthenoteratozoospermia, especially for younger participants.